Sistem Pendukung Keputusan Penerima Bantuan Pangan Non Tunai Dengan Metode Hybrid AHP- SAW - Arianto, Satria Rizki; Siswanti, Sri; Saptomo, Wawan Laksito Yuly (Jurnal Transformatika, 2020)
Food Aid Non-Cash given to the family of Beneficiaries. The current Non-Cash Food Assistance System still has many obstacles, such as the proposed citizen data directly entering the Poor Citizen data, some residents are quite capable of receiving help and there is no method to decide acceptance criteria. The research aim is the use of the Analytical Hierarchy Process and Simple Additive Weighting methods used in supporting the decision to decide the receipt of non-cash food aid. Analytical Hierarchy Process method to decide the weight and Simple Additive Weighting to decide the ranking of each alternative.  In this research Author using Mc Call testing with the overall results of  the assessment of  respondents with an average of 3.3 with a percentage of 82.5% categorized as Very Good. In this study the authors succeeded in applying the Analytical Hierarchy Process and Simple Additive Weighting methods for the food aid recipient process. The result of this research successfully implemented application for the choice of recipients of food help at the  makamhaji  village